Gay and lesbian literature in the classroom: Can Gay themes overcome heteronormativity? - April M Sanders; Janelle B. Mathis (Journal of Praxis in Multicultural Education, 2013)
Lesbian, gay, bisexual, and transgender (LGBT) characters do exist in children’s and young adult literature, yet there is a lack of classroom exposure to such literature. Educational organizations have realized the need for dispelling prejudices about LGBT people by including such texts in the classroom as well as discussions regarding LGBT themes and characters in the books. Yet the practice of simply including diverse texts without discussing LGBT issues could cause greater marginalization for students because the silence regarding LGBT issues and characters encourages the practice of heteronormativity. This inquiry examined a range of children’s and adolescent books that could be used in classroom discussions to develop insight about LGBT themes and characters in order to understand if the texts were saturated with LGBT themes and characters to the point that teachers and students could not avoid the LGBT factors while reading.
Keywords: amériques; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; régions géographiques; science de l'éducation; systèmes d'oppressions; thématiques; états-unis